The Origins of Islamic Reformism in Southeast Asia - Azra, Azyumardi (Allen & Unwin, 2004)
Islamic renewal and reformism is an ongoing process which is commonly thought to have started only in the twentieth century. Professor Azra's menticulous study, using sources from the Middle East itself, shows how scholars in the seventeenth and eighteenth centuiries were reconstructing the intellectual and socio-moral foundation of Muslim societies.